World of personal names in the mongol-language worldview: etymological and ritual aspects - E. U. Omakaeva (Nomadic Civilization: Historical Research, 2024)
The article is devoted to identifying the national and cultural specifics of Kalmyk and Mongolian personal names. Anthroponymy has great educational and cultural-historical value. It is a kind of history of the life of an ethnic group, a real encyclopedia of folk life, conveying its unique flavor, the originality of material and spiritual culture, unwritten rules of behavior in the family and society. The study of the features of personal names is especially productive within the framework of linguoculturology and ethnolinguistics. The object of the study is anthroponymic linguocultural codes, the subject is anthroponyms as their representatives. Personal names of Kalmyks and Mongols are closely related to the material and spiritual culture of nomads. Many anthroponyms arose as a result of the onymization of appellative vocabulary (names of animals and plants, Buddhist terms, etc.), as well as transonymization (the transition of theonyms into anthroponyms). Personal names are of particular interest to the author both from the point of view of their special role in the onomastic space and from the point of view of their representation in the languages serving Buddhist culture (in particular, in Kalmyk and Mongolian). The article provides a semantic and etymological analysis of anthroponyms in the context of the birth rite among the Kalmyks. It is shown that this class of borrowed onomastic vocabulary deserves a systematic description taking into account the Buddhist context, and, accordingly, the Sanskrit-Tibetan parallels. Most of the considered names are descriptive names and desirative names, they are representatives of basic linguocultural codes (primarily biomorphic, abstract and spiritual-religious).